Solove the solution.

Question

Asked 2/11/2013 12:05:52 PM

Updated 4/26/2014 11:12:28 AM

1 Answer/Comment

Flagged by yeswey [4/26/2014 11:10:45 AM]

s

Question

Asked 2/11/2013 12:05:52 PM

Updated 4/26/2014 11:12:28 AM

1 Answer/Comment

Flagged by yeswey [4/26/2014 11:10:45 AM]

Rating

8

5(3z-1)-4(z+2)=6(z+1)

15z - 5 - 4z - 8 = 6z + 6

11z - 13 = 6z + 6

11z - 6z = 6 + 13

5z = 19

z = 19/5

15z - 5 - 4z - 8 = 6z + 6

11z - 13 = 6z + 6

11z - 6z = 6 + 13

5z = 19

z = 19/5

Added 4/26/2014 11:12:28 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/26/2014 1:37:52 PM]

2(x-2)-6=0 what is the equation x= **Weegy:** 2(x-2)-6=0 ; 2x-4=6 ; 2x=10 ; x=10/2 ; x=5 (More)

Question

Expert Answered

Asked 2/11/2013 10:25:28 AM

0 Answers/Comments

-(z+7)+(6z+1)=-4(z+1). What is the soultion **Weegy:** -6 + 5z = -4 + -4z
(More)

Question

Expert Answered

Updated 2/12/2014 7:52:13 PM

1 Answer/Comment

-(z+7)+(6z+1)=-4(z+1)

-z - 7 + 6z + 1 = -4z - 4

5z - 6 = -4z - 4

5z + 4z = -4 + 6

9z = 2

z = 2/9

The solution is 2/9.

-z - 7 + 6z + 1 = -4z - 4

5z - 6 = -4z - 4

5z + 4z = -4 + 6

9z = 2

z = 2/9

The solution is 2/9.

Added 2/12/2014 7:52:13 PM

This answer has been confirmed as correct and helpful.

Solve the equation and solve the solution? 5(3z-1)-4(z+2)=6(z+1) The solution is z=? **Weegy:** 5(3z-1)-4(z+2)=6(z+1),
11z-13=6z+6,
11z - 6 = 6 + 13,
5z = 19, The solution is z = 19/5 (More)

Question

Expert Answered

Updated 6/19/2014 10:40:12 PM

0 Answers/Comments

32,513,708

questions answered

There are no comments.